Inter and intra-individual variation in skeletal DNA preservation in buried remains. (January 2020) - Emmons, Alexandra L.; Davoren, Jonathan; DeBruyn, Jennifer M.; Mundorff, Amy Z.
Highlights: Human DNA concentrations in buried remains varied by individual and anatomical region. Foot bones, specifically cuneiforms, performed best in DNA tests and are recommended for skeletal sampling from buried, non-commingled remains. Not a single long bone ranked among the top 10 most successful elements for human DNA testing for any individual. Total bacterial and fungal gene abundances in bone, as a proxy for microbial loading, were not reliable predictors of human DNA concentration. Abstract: Our ability to identify skeletal remains often relies on the quality and quantity of DNA extracted from bone and teeth. Current research on buried remains has been retrospective, and no study to our knowledge has comprehensively assessed both intra-individual and inter-individual variation in human skeletal DNA from all representative skeletal element types recovered from a burial. Three individuals were interred together in a single grave for four years. Following disinterment, skeletal DNA was extracted, quantified, and GlobalFiler™ results were produced from 49 bones per skeleton, representing all bone types. Multiple sites per bone were also tested to determine intra-bone variability. Co-extracted bacterial and fungal DNA were quantified to determine microbial loads in the bones. Results show that the small, cancellous bones of the feet outperformed other bones in terms of DNA yield, measured as nanograms per gram of bone powder, and short tandem repeat (STR) profile completeness. The cuneiforms, in particular, had consistently high human DNA yields for all three individuals. DNA yield varied by individual and depth within the grave, with the shallowest individual demonstrating the highest DNA yields While the feet exhibited the greatest variation in DNA yield across bone type and sampling site, they also demonstrated some of the highest DNA yields and the most complete STR profiles, evoking a re-evaluation of their use for skeletal DNA sampling and analysis.